Penggunaan Artificial Salt Lick dalam Mitigasi Interaksi Negatif Gajah Sumatera (Elephas maximus sumatranus) dengan Manusia di Wilayah Blok I Konsesi PT Alam Bukit Tigapuluh: The Use of Artificial Salt Lick in Mitigating Negative Interactions Between Sumatran Elephant (Elephas maximus sumatranus) and Humans in Block I of PT Alam Bukit Tigapuluh Concession - Qosyim, Muhammad Rizki; Hamzah, Hamzah; Zuhdi, M.; Syarifuddin, Hutwan; Achmad, Eva; Marwoto, Marwoto (Jurnal Silva Tropika, 2026)
ABSTRACT Habitat fragmentation driven by continuous human population growth and land expansion has intensified human–Sumatran elephant conflict (Elephas maximus sumatranus) in Jambi Province, particularly within the concession area of PT Alam Bukit Tigapuluh (PT ABT). This study aimed to evaluate the effectiveness of artificial salt licks as a conflict mitigation strategy by modifying elephant movement patterns and ranging behavior. Employing a mixed-methods approach (quantitative and qualitative), the study was conducted in Block I of the PT ABT concession from December 2024 to June 2025. Ten artificial salt lick sites were established based on GPS collar data analysis and Kernel Density Estimation (KDE) mapping, strategically positioned away from areas of human activity. Data were collected through track observations, camera trap (CT) deployment, and Focus Group Discussions (FGDs) with local communities. The results demonstrated that the artificial salt licks successfully attracted Sumatran elephants, with the highest visitation intensity recorded at sites characterized by gentle topography. Track identification and camera trap recordings confirmed group movements of elephants around the salt lick areas, indicating a shift in movement routes away from settlements and agricultural lands. Local communities also reported a significant decline in negative human–elephant interactions following the intervention. These findings suggest that artificial salt licks are effective in redirecting elephant ranging behavior, contributing to conflict reduction and supporting elephant conservation through the provision of alternative mineral resources.   Keywords: artificial salt lick, conflict mitigation, habitat management, human–elephant conflict, sumatran elephant   ABSTRAK Fragmentasi habitat akibat pertumbuhan populasi manusia dan ekspansi lahan terus-menerus telah memicu konflik antara manusia dan Gajah Sumatera (Elephas maximus sumatranus) di Provinsi Jambi, khususnya di areal konsesi PT Alam Bukit Tigapuluh (PT ABT). Penelitian ini bertujuan mengevaluasi efektivitas implementasi artificial salt lick (jilat garam buatan) sebagai strategi mitigasi konflik dengan memodifikasi pola pergerakan dan perilaku jelajah gajah. Menggunakan metode mixed methods (kuantitatif dan kualitatif), penelitian ini diterapkan di Blok I konsesi PT ABT pada Desember 2024–Juni 2025. Sepuluh titik artificial salt lick ditempatkan berdasarkan analisis data GPS collar dan pemetaan Kernel Density Estimation (KDE), menjauhi area aktivitas manusia. Data dikumpulkan melalui observasi jejak, pemasangan kamera jebak (CT), dan Focus Group Discussion (FGD) dengan masyarakat. Hasil menunjukkan bahwa artificial salt lick berhasil menarik Gajah Sumatera, dengan intensitas kunjungan tertinggi di lokasi bertopografi landai. Identifikasi jejak dan rekaman CT mengkonfirmasi pergerakan gajah secara berkelompok di area sekitar salt lick, mengindikasikan pengalihan jalur dari pemukiman dan lahan pertanian. Masyarakat mengonfirmasi penurunan drastis interaksi negatif pasca-intervensi. Temuan ini menunjukkan bahwa artificial salt lick efektif dalam mengalihkan perilaku jelajah gajah, berkontribusi pada pengurangan konflik, dan mendukung konservasi gajah melalui penyediaan sumber daya mineral alternatif.   Kata kunci: artificial salt lick, gajah sumatera, konflik manusia-gajah, mitigasi konflik, pengelolaan habitat